(untitled) (Chittagong University Journal of Biological Sciences, 2025)
Rice has been implicated as a major dietary source of arsenic exposure. Under this study, total arsenic levels of 100 Bangladeshi rice grain samples collected from wholesale and retail markets in Chattogram Division were measured by Hydride Generation Atomic Absorption Spectrometry (HG-AAS). Twenty-five foreign rice types were used as controls. The mean arsenic concentration in the samples was 0.18 μg/gm, falling within the “global normal range” of 0.08 - 0.20 μg/gm. None of the Bangladeshi samples exceeded the recommended maximum limit of 1.0 μg/gm. We estimated that rice contributed 37.29% of the maximum tolerable daily intake (MTDI) of arsenic in local consumers. Cooking rice samples containing arsenic below detection limit with water sample containing 216 μg/L arsenic resulted in marked elevation of arsenic content in the cooked samples (0.79 to 1.08 μg/gm). The present findings suggest that arsenic exposure through rice consumption should not be neglected while devising mitigation policies. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 93-101, 2025